Efficiency of disinfectants against Rotavirus in the presence and absence of organic matter - Chandler-Bostock, Rebecca; Mellits, K.H. (Wiley, 2015)
Rotavirus is an enteric pathogen that causes morbidity and mortality in young mammals, including pigs. Outbreaks of rotavirus on commercial farms have a significant economic impact in terms of losses in production. Effective cleaning and disinfection along with good farm management can reduce rotavirus contamination in the environment, and decrease the chance of outbreaks of disease. This study investigated the efficacy of six commercial disinfectants against MS2 bacteriophage and Group A porcine rotavirus, in the presence of high and low levels of organic matter to simulate the farm environment. A phenolic-based disinfectant (Bi-OO-cyst) was effective at all levels of organic matter concentrations. Iodophore based disinfectants did not have a significant virucidal effect against rotavirus under any conditions. For peroxygen compound-based disinfectants and glutaraldehyde-based disinfectants, organic matter load made a significant difference in reducing efficacy. This highlights the importance of thorough cleaning with detergent before disinfection to reduce viral contamination on the farm and decrease rotavirus disease incidence in pigs.